Ekpe Fraternity as a Political and Social Machinery for Security and Development in Old Calabar - Eke, Nta Effiong; Bassey, Inyang Etim; Ellah, Timothy Ogbang; Utulu, Celestine Benedict (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Since the inception of mankind, politics has posed a paramount challenge, constituting the art or science of governance and profoundly influencing the development of societies. This perennial issue revolves around the prudent and astute formulation and implementation of measures to advance the public welfare of nations, persisting indefinitely unless sincere governance prevails. Human nature, inherently characterized by selfishness, greed, and covetousness, has endured across civilizations, thwarting efforts to transcend these inherent traits. Consequently, humanity seeks various means to alleviate these afflictions, resorting to coercion, deception, hypocrisy, and even malevolent forces in desperate attempts to address societal challenges. Religion, encompassing Christianity, Islam, Hinduism, and others, has been wielded by individuals to subjugate nations into compliance, with rulers often invoking divine origins to assert control, while clandestine societies emerge for similar ends. This study aims to critically examine the role of the Ekpe fraternity as a political and social apparatus in fostering peace and development in Old Calabar. Employing an interdisciplinary approach to historical analysis, the research draws upon diverse disciplines for data collection. Ultimately, the investigation unveils the myriad strategies employed by the Ekpe fraternity to uphold security and development in Old Calabar, shedding light on the challenges encountered in fulfilling these functions.